Strategies to prevent medical errors by nursing interns: a qualitative content analysis - Nastaran Heydarikhayat; Nezar Ghanbarzehi; Kimiya Sabagh (BMC, 2024)
Abstract Background Nursing interns often face the serious challenges and stress of clinical training. Identifying effective strategies in reducing medical errors can improve student performance and decrease patient risk and injury from errors. The purpose of this study was to identify strategies to prevent medical errors by nursing interns in Medical Universities in Sistan and Baluchistan, Southeast of Iran. Methods This is a qualitative study using a content analysis approach. Purposive sampling was used. The study was conducted in 3 medical universities. Ten nursing interns participated in this study. Open-ended, semi-structured, and face-to-face, interviews were used to explore the experience of nursing interns about strategies to prevent medical errors during their internship. Results Findings include 20 subcategories, 6 categories and one theme. The main theme is "strategies to prevent medical errors during internship". Six categories included "strategies to prevent medical errors during internship". These included "Professional acceptance and support", "Revision of the implementation of the educational curriculum", "Retraining courses for challenging skills", "Creating learning opportunities" "Professionalization", and "Facilities and requirements". Conclusions Preventing medical errors requires different strategies before and during nursing internship. Error prevention strategies include retraining and preparatory courses for challenging areas, evaluation of students' performance, and accepting students as members of the health care team, respecting and supporting them and protecting their rights. Learning from medical errors, analysis and reflection on errors should be part of the curriculum during the internship.